Successful aging, change in sexual interest and sexual satisfaction in couples from four European Countries - Stulhofer, Aleksandar (2019)
Although the importance of sexuality and physical intimacy for well-being of older adults has been recognized, the role of sexuality in successful aging (SA) has been largely neglected. Building on our previous work, here we further validated a three-dimensional model of SA and examined its associations with sexual satisfaction and change in sexual interest among older heterosexual couples (aged 60–75 years). Participants were recruited in a probability-based survey, which was carried out in 2016–2017 in four European countries. Using structural equation modeling of the Actor–Partner Interdependence, we observed significant relationships between SA and sexual satisfaction for both male and female partners across countries. Among women, their retrospectively assessed change in sexual interest over the past 10 years was consistently associated with sexual satisfaction. Partner effects were gender-specific: male partners’ SA was significantly related to their female partners’ change in sexual interest, which in turn was linked to male partners’ sexual satisfaction. The findings point to substantial ties between successful aging and sexuality in older European couples. Taking into account the prevalent stereotypes about old age and sexuality, this study’s findings can assist professionals working with aging couples.